Rediscovery of Isonandra villosa Wt. of Sapotaceae from Velugonda and Kambakkam Hills of Andhra Pradesh, India - Lalithamba, A.; Chalapathi Rao, P. V.; Sivarama Prasad, N. V. (Indian Forester, 2020)
No Abstract.